Synonymy of Crossodactylus bokermanni Caramaschi & Sazima, 1985 with Crossodactylus trachystomus (Reinhardt & Lütken, 1862) and description of a new species from Minas Gerais, Brazil (Anura: Hylodidae) - Pimenta, Bruno V.s.; Caramaschi, Ulisses; Cruz, Carlos Alberto Gonçalves (Zootaxa, 2015)
The analysis of the external morphology variation in Crossodactylus bokermanni, C. trachystomus, and in unidentified specimens from 14 localities along the southern region of the Serra do Espinhaço, state of Minas Gerais, Brazil, revealed that all of these forms belong to the same taxon. Crossodactylus bokermanni is considered a junior synonym of C. trachystomus, whose holotype is redescribed and figured. The population from Serra da Canastra, western Minas Gerais, previously referred to as Crossodactylus cf. trachystomus, is herein described and figured as Crossodactylus franciscanus. Its advertisement call is redescribed and compared to those known for the genus.